1999
DOI: 10.1097/00005176-199911000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in Infants and Children: Evaluation and Treatment

Abstract: This report, which has been endorsed by the Executive Council of the North American Society for Pediatric Gastroenterology and Nutrition, has been prepared as a general guideline to assist providers of medical care in the evaluation and treatment of constipation in children. It is not intended as a substitute for clinical judgment or as a protocol for the management of all patients with this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
181
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(187 citation statements)
references
References 59 publications
3
181
0
3
Order By: Relevance
“…Constipation is a common disorder in childhood which accounts for 25% of the visits to pediatric gastroenterology clinics and 3% of referrals to teaching hospital clinics (1,2). The pathophysiology of constipation in children is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is a common disorder in childhood which accounts for 25% of the visits to pediatric gastroenterology clinics and 3% of referrals to teaching hospital clinics (1,2). The pathophysiology of constipation in children is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with several adverse outcomes throughout life. Constipation generally is defined by the hard nature of the stool, the pain associated with its passage, or the failure to pass three stools per week (1). It is a very common frustration for children, parents, and physicians.…”
mentioning
confidence: 99%
“…In a series of long term follow-up studies of children presenting under the age of 5 years to a specialist clinic in Iowa, 50% recovered within one year and 65-70% recovered within two years; the remainder required laxatives for daily bowel movements or continued to soil for several years. 10 In a longitudinal study of 418 children with a median age of 8.0 years at enrolment, a third of those followed up beyond puberty continued to have severe constipation.…”
Section: Box 1 Terminology Recommended By Pacct Groupmentioning
confidence: 99%
“…9 Pyschosocial factors are often suspected, and some studies have reported higher levels of behavioural disorders in children with constipation, with or without incontinence, though it remains unclear whether these precede the problem or are a maintaining factor. 10 Chronic constipation can lead to progressive faecal retention, distension of the rectum, and loss of sensory and motor function.…”
mentioning
confidence: 99%